What would Jesus deconstruct? : the good news of postmodernism for the church - Caputo, John D. (Grand Rapids, Mich. Baker Academic, 2007)
Uses the postmodern theme of deconstruction to suggest a constructive and provocative way forward for the church
Keywords: Postmodernism -- Religious aspects -- Christianity. Christentum Bürger, Christa -- 1935- -- Postmoderne